Concentrating Solar Thermal storage using metal hydride: Study of destabilised calcium hydrides - Griffond, Arnaud Camille Maurice (Curtin University, 2019)
This manuscript aims to study destabilised calcium hydrides system as thermal energy storage for concentration solar power. Using thermodynamic calculation and cost estimation, 3 different systems has been selected for in depth analysis of their thermal properties, the chemical reaction has been observed using in-situ synchrotron as well as their sorption properties. This laboratory scale analysis is used to select a promising material for on field application.